Assessment of Dental Anomalies in a Pediatric Population: A World Health Organization–Based Approach - Beyza Ecem Alkaç Ekici; Sümeyra Akkoç; Merve Uluakay (European Annals of Dental Sciences, 2026)
ABSTRACT Purpose: Dental anomalies refer to congenital, developmental, or acquired deviations from normal tooth development. The present study aims to evaluate the prevalence of dental anomalies and associated factors in a pediatric population using panoramic radiography.Materials and Methods: In this retrospective study, panoramic radiographs obtained from patients aged 6–15 years were evaluated. The number of teeth affected by dental anomalies, their localization within the jaws, as well as the patients’ age, sexes, and the type of anomalies were recorded during the evaluation conducted based on dental anomalies in the International Classification of Diseases-11. Data analyses were performed using IBM SPSS V23. Group comparisons of categorical variables were conducted using Chi-Square and Fisher’s exact tests, with significance set at p < 0.05.Results: A total of 1505 panoramic radiographs were included in the analysis. The results revealed that at least one dental anomaly was present in 26.3% of the patients. Among the dental anomalies identified, dilaceration of tooth (13.16%) and hypodontia (5.65%) were determined to be the most prevalent. While no significant difference was found between the sexes in terms of the presence of anomalies, a significantly higher prevalence was observed in the age group of 12-15 years and in the maxilla (both p